Determinants of Student’s Saving Interest at Islamic Bank - Sukarmin Hidayat; Syahfitri Suryaningsi Welkom; Anggun Pratiwi (Universitas Negeri Gorontalo, 2023)
Purpose: This study aimed to determine the effect of knowledge, products, and promotions on the students’ saving interest at Islamic banks.Design/Methodology/Approach: This research used quantitative analysis. The population was Hybrid Learning Students of the undergraduate Management Program in the Faculty of Economics and Business, University of Al-Azhar Indonesia, totaling 1.314. The survey method with the sampling technique used is accidental sampling. The number of samples was 100 students who saved in Islamic banks. The research method used multiple linear regression analysis.Findings: Based on the results of statistical tests, the knowledge has a significant positive effect on students' saving interest at Islamic banks, the product has a significant positive effect on students' saving interest at Islamic banks, and also, the promotion has a significant positive effect on students' saving interest at Islamic banks.